STRUKTUR KOMUNITAS MAKROZOOBENTOS DI PERAIRAN SUNGAI BINGAI KECAMATAN BINJAI BARAT KOTA BINJAI (Community Structure of Macrozoobenthos in the River Bingai at West Binjai Subdistrict of Binjai City) - Navisa Fairuz; Hasan Sitorus; Indra Lesmana (AQUACOASTMARINE, 2015)
River Bingai is used variety of human activities that may increase water pollution which effect on the biological, chemical and physical of water. The objective of the research are to determine the macrozoobenthos and its related to chemical and physical parameters. The method used in this research is purposive sampling where river waters Bingai used as a research location. Based on the research was found 3 classes and 7 genusses of macrozoobenthos in waters of River Bingai, West Binjai Subdistrict. The gastropods was the most abundance in the river. Index of species diversity showed lower value that means water quality was moderate. The evenness index and dominan index was coherent to water quality condition.Keyword : Macrozoobenthos Community, Water Quality, River Bingai.